Sexual Harassment and Coping Strategies Among Malay Female Administrative and Diplomatic Officers - Ahmad, Noor Azima (2006)
With forecasted participation rate of 45.8 per cent in 2005, Malaysian women have contributed significantly to the development of the Nation. Thus, their well-being and basic human rights to have a safe and conducive workplace should be assured: including from sexual harassment. Sexual harassment is noted by the United Nations as a form of discrimination and violence against women in various conventions that Malaysia has acceded to; primarily the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). Literature on sexual harassment suggests that one in two women would experience some forms of sexually harassing behaviour during her working life. This is a qualitative research involving 16 female respondents working in the public sector. Observation is mainly drawn from interviews with the respondents. In the interest of triangulation, informal interviews with their friends and colleagues were also conducted. Besides that, key informants also provided required background information. It is a study of power relations between the harassers and the victims at public workplaces. The research examines the incidences and reactions to sexual harassment and the types of coping strategies employed by the respondents who are in the subordinate positions in the organizational structure. The central argument is that the issue of power and powerlessness is embedded in the work culture which oppresses women's rights to have a safe and conducive working environment. The study also seeks to examine the factors influencing the types of coping strategies used by the respondents. Findings revealed that no one reported a one-time harassment. Instead, all the respondents faced numerous types of harassment for a considerable length of time. As for types of coping, a number of coping strategies were simultaneously used by the respondents as they saw fit and most effective at that particular time. Some coping patterns emerged. While there are some respondents who were empowered enough to stand for their rights, most preferred to keep quiet as to avoid further complications and repercussions at the workplace. This supports previous studies that women tend not to seek advocacy intervention. Only in severe harassment cases that they did so. Respondents in this study avoided advocacy-seeking since previous cases reported to higher authority yielded no favourable response. There are some exceptional cases where respondents went along with the harassers due to several factors, including childhood upbringing and family background. The main factors influencing their decision on coping strategies were power differential, socialization and background, severity, personal empowerment and personality, and office environment. The study concludes that sexual harassment is an intricate form of sexual violence and is mostly all about men in power and un-empowered women. To minimize incidences of sexual harassment at public workplaces, people need to have basic respect to others as found in the tenets of all religion. Besides that, more gender sensitivity courses should be conducted, with massive awareness campaign on the Sexual Harassment Guideline introduced by the PSD in August 2005. Only then, more harmonious and safer working environment could be achieved in the public sector.